2003
DOI: 10.1057/palgrave.ces.8100005
|View full text |Cite
|
Sign up to set email alerts
|

Institutions Matter in Transition, But So Do Policies

Abstract: This paper analyses the importance of developing market-enhancing institutions for restoring economic growth in transition economies during 1991-98. The paper's main finding is that the development of an institutional framework has indeed a significant positive impact on growth, but that progress in achieving macroeconomic stabilisation and implementing broad-based economic reforms remain the key determinants of growth in transition economies. Comparative Economic Studies (2003) 45, 2-24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 13 publications
(9 reference statements)
1
59
0
1
Order By: Relevance
“…There also already exists a wealth of research on institutional development in 1 Moreover, Fang et al (2014) do not include CIS countries in their dataset, which I do here. Bulgaria, 2006Bulgaria, -2012 transition, with work such as Brunetti et al (1997), Havrylyshyn and van Rooden (2003), and Hartwell (2013) taking a methodical look at the various institutions needed for a market economy and how they impacted different parts of the real economy in transition. Linking these two strands of research together is the diverse body of work on how institutions would influence financial outcomes: in addition to Demirgüç-Kunt et al (2004) and Athanasoglou et al (2008), very recent work from Fang et al (2014) has already found some evidence of the impact of institutions on bank stability in transition.…”
Section: Bank Profitability In Transition: the Role Of Institutionsmentioning
confidence: 99%
“…There also already exists a wealth of research on institutional development in 1 Moreover, Fang et al (2014) do not include CIS countries in their dataset, which I do here. Bulgaria, 2006Bulgaria, -2012 transition, with work such as Brunetti et al (1997), Havrylyshyn and van Rooden (2003), and Hartwell (2013) taking a methodical look at the various institutions needed for a market economy and how they impacted different parts of the real economy in transition. Linking these two strands of research together is the diverse body of work on how institutions would influence financial outcomes: in addition to Demirgüç-Kunt et al (2004) and Athanasoglou et al (2008), very recent work from Fang et al (2014) has already found some evidence of the impact of institutions on bank stability in transition.…”
Section: Bank Profitability In Transition: the Role Of Institutionsmentioning
confidence: 99%
“…Later empirical work reinforced the importance of initial conditions, but emphasized that they could often be overcome with good policy [Havrylyshyn and Van Rooden, 2003], or that both mattered [Heybey and Murell, 1998]. Others argued that given the importance of other factors, the data showed that shock therapy, or even policies overall, cannot be relied upon alone to bring gains [Radulescu and Barlow, 2002], though also concluded that the role of market institutions needs to be looked at more closely.…”
Section: Factors Affecting Transitionmentioning
confidence: 99%
“…Одна-ко за последние пятнадцать лет круг эмпирических исследований по влиянию институтов на развитие переходных экономик существенно расширился. В большинстве из них наблюдается положительная взаимосвязь между качеством национальных инсти-тутов и темпами экономического роста [Hartmann, Moers, 1999;Havrylyshyn, van Rooden, 2000;Ahrens, Meurers, 2000;Raiser et al, 2001;Beck, Laeven, 2005].…”
Section: концептуальные рамки анализаunclassified